Penambahan Kode Tanwīn Waṣl Dalam Mushaf Al-Qur’an Braille: Analisis Semiotika Charles Sanders Peirce - Firmananda, Muhammad Fikri; Sihabudin, M. (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
Accessibility of the Qur'an for visually impaired individuals remains a serious challenge, as evidenced by the low number of blind Indonesian Muslims who can read the Braille Qur'an. This study aims to examine the form, meaning, and function of the tanwīn waṣl symbol in the Braille Qur'an through the semiotic framework of Charles Sanders Peirce. The subject of this research is the tanwīn waṣl symbol in the Standard Braille Qur'an published by the Ministry of Religious Affairs of the Republic of Indonesia through the Lajnah Pentashihan Mushaf Al-Qur'an. This qualitative library research employs descriptive qualitative analysis based on Peirce's triadic framework, encompassing representamen, object, and interpretant. The findings indicate that as representamen, the tanwīn waṣl symbol takes the form of a raised-dot pattern 1, 2, 4, 5, 6, perceivable tactilely. As object, it refers to a phonological phenomenon wherein tanwīn meets hamzah waṣl, requiring the pronunciation of the letter nun with vowel i. As interpretant, the symbol produces layered understanding: a tactile warning signal for novice readers, a specific articulation guide for intermediate readers, and a representation of the broader tajwīd rule system for advanced readers.